Assessment of body fat percentage in Emirati females: a comparative analysis of BIA vs. DXA - Haroun, Dalia; Ehsanallah, Aseel (Frontiers in Nutrition, 2026)
IntroductionObesity is a significant health issue in the UAE. Accurate body composition assessment is crucial for managing obesity-related health risks. This study aimed to evaluate the agreement between bioelectrical impedance analysis (BIA) and dual-energy X-ray absorptiometry (DXA) in measuring body composition among Emirati females.MethodsThis cross-sectional study involved 95 healthy Emirati females aged 17–27 years. Paired samples t-tests, correlation analyses, and Bland-Altman plots were used to compare the two methods (BIA vs. DXA).ResultsBIA significantly underestimated % fat and fat mass (FM) while overestimating fat-free mass (FFM) compared to DXA. The mean difference in % fat was −14.1% (p < 0.001), and the mean difference in FFM was +8.2 kg (p < 0.001). Despite strong correlations between BIA and DXA measurements (r = 0.855 for % fat, r = 0.984 for FM, and r = 0.929 for FFM), Bland-Altman plots indicated poor agreement, with wide limits of agreement.ConclusionBioelectrical impedance analysis remains valuable for obesity assessment in large-scale studies and clinical settings due to its non-invasive, easy-to-use, and cost-effective characteristics. The results show that the in-built prediction equations cannot adequately predict the % fat, FM, and FFM for this sample. Future research should focus on developing and validating BIA-specific equations tailored for Emiratis.